Enactment, politics, and truth Pauline themes in Agamben, Badiou, and Heidegger - Cimino, Antonio 1979- (Bloomsbury Academic, 2018)
"Analyzes the interpretations of Pauline faith by Heidegger, Badiou, and Agamben"...